KOMUNIKASI PERSUASIF KONSELOR LAKTASI KOMUNITAS CINTA ASI RIAU UNTUK MENINGKATKAN PARTISIPASI IBU DALAM PROGRAM ASI EKSKLUSIF DI KOTA PEKANBARU - Cicilia Margarettha S; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The high infant mortality rate is still a serious problem in Indonesia. Overcoming this problem the government promote the Exclusive Breastfeeding Program and set it in the Government Regulation Number 33 of 2002. Cinta ASI Riau Community as a support group in Exclusive Breastfeeding Program then actively doing persuasive communication to convince mothers to breastfeeding their babies. The purpose of this research is to know the persuasive communication activity conducted by Lactation Counselor of Cinta ASI Community in the aspect of credibility of persuader, persuasive message, media selection and the resultant effect in the effort to increase mother participation in Exclusive Breastfeeding Program in Pekanbaru City.This research uses qualitative research method with Applebaum & Anatol’s persuasive communication model. Determination of the research informant was conducted based on purposive techniques, amounted to 6 person. Data collection techniques include interviews, observation and documentation. Data analysis techniques use Miles and Huberman’s interactive data models.The results show that Lactation Counselor of Cinta ASI Riau Community has credibility as a persuader that built from skill aspect through training and certification program and trustworthy aspect from counselor action and practice. Persuasive messages delivered consist of verbal messages including clarity, preciseness, and accuracy in providing information and education about the program. While the nonverbal message seen from the body notion in the form of counselor’s body movements; paralanguage of counselor's intonation; the sensitivity of the skin by giving a touch on the mother's shoulder that displays the closeness and counselor’s care; and use the artifacts with props and counselor appearance. The media selection consists of direct media conducted on home visit/counseling and indirect media using brochures, banners and social media Facebook, Twitter AIMI_Riau and WhatsApp Group Cinta ASI Riau. The resultant effect, first is cognition effect by increased knowledge, understanding and awareness of the mother. Second, affection effect is the mother's consideration about the importance of breastfeeding for the baby and third, conation effect with the mother's actions in breastfeeding on her baby.Keywords: Persuasive Communication, Lactation Counselor, Exclusive Breastfeeding.